Invisible excess of sense in social interaction - Koubová, Alice (Frontiers in Psychology, 2014)
The question of visibility and invisibility in social understanding is examined here. First, the phenomenological account of expressive phenomena and key ideas of the participatory sense-making theory are presented with regard to the issue of visibility. These accounts plead for the principal visibility of agents in interaction. Although participatory sense-making does not completely rule out the existence of opacity and invisible aspects of agents in interaction, it assumes the capacity of agents to integrate disruptions, opacity and misunderstandings in mutual modulation. Invisibility is classified as the dialectical counterpart of visibility, i.e., as a lack of sense whereby the dynamics of perpetual asking, of coping with each other and of improvements in interpretation are brought into play. By means of empirical exemplification this article aims at demonstrating aspects of invisibility in social interaction which complement the enactive interpretation. Without falling back into Cartesianism, it shows through dramaturgical analysis of a practice called “(Inter)acting with the inner partner” that social interaction includes elements of opacity and invisibility whose role is performative. This means that opacity is neither an obstacle to be overcome with more precise understanding nor a lack of meaning, but rather an excess of sense, a “hiddenness” of something real that has an “active power” (Merleau-Ponty). In this way it contributes to on-going social understanding as a hidden potentiality that naturally enriches, amplifies and in part constitutes human participation in social interactions. It is also shown here that this invisible excess of sense already functions on the level of self-relationship due to the essential self-opacity and self-alterity of each agent of social interaction. The analysis consequently raises two issues: the question of the enactive ethical stance toward the alterity of the other and the question of the autonomy of the self-opaque agent.